Development of a glucose sensitive insulin delivery PLGA microparticle system - Dino, Mohamad Hadid Amshah (2018)
This project details the investigation done to formulate insulin-loaded PLGA microparticles for responsive insulin delivery. The formulations are to be tested for glucose specificity as a function of particle porosity later on in the investigation. The glucose responsive characteristic of the PLGA microparticle was modulated via incorporation of 4-formylphenyl boronic acid (4-FPBA) through conjugation with chitosan. Boronic acid moieties present in 4-FPBA are known to be sensitive to diols, such as glucose and fructose and is used here to provide the glucose sensing characteristic of the PLGA microparticles while chitosan is used as the anchor and readily forms nano- and micro-particles through ionic gelation with a suitable cross-linkers. The conjugation of 4-FPBA and chitosan proceeded through the Schiff's base method through N-reductive alkylation. The conjugates were characterized using Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC) and field emission scanning electron microscope (FESEM) analysis to ascertain the extend of bonding of the conjugate. The double solvent evaporation method was used to formulate porous and non-porous formulation. The non-porous formulation was found to be stable, discrete with no agglomeration seen through SEM analyses. Porosity was induced in the microparticle formulation through the use of parogens. Through optimization, stable and porous PLGA microparticles were formulated by enhancing the pores formed via exposure to ethanolic- NaOH. The glucose absorption of the PLGA microparticle samples was successfully measured through an indirect method utilising curcumin to detect 4-FPBA content in the microparticle sample. It was found that the increase in surface area afforded by the porous PLGA microparticle caused more of the 4-FPBA tagged chitosan to be incorporated within particles which resulted in higher 4-FPBA content readily available in the porous microparticle sample. The higher 4-FPBA content correlates to a higher glucose sensitivity for the porous PLGA microparticles as observed in the higher insulin release profile obtained when compared to the non-porous microparticles. Porosity plays a vital role in increasing the glucose responsivity of the microparticles as the porous microstructure exposes more 4-FPBA to glucose and hence enhance the reactivity, allowing more of the incorporated insulin to be release as a consequence.